ANALISIS AKTUALISASI KEBUTUHAN SERTIFIKASI GURU TERHADAP KINERJA GURU DI SD NEGERI 091254 BATU ONOM - Simanjuntak, Melvin M; Melinda Hutagalung; Cicilia Pebriana Hutagalung; Dewi Sari Bunga Sipayung; Cindy Clara Tinambunan; Yasica Hana Damaris Sinaga; Elisabeth M. Sitorus; Sondang Valentina Simanjuntak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to find out and explain how teacher certification analyzes teacher performance at SD N. 091254 Batu Onom. The population taken in this research were 5 certified teachers and the sample was the entire population. The analytical method used in this research is a quantitative approach. By reviewing and analyzing data objectively according to data found in the field. Then the data collected from the research results is described in the form of words. Data collection techniques through observation. Interviews, questionnaires, documentation. The results of the research show (1) that teacher certification has a positive effect on teacher performance, (2) Teacher performance at SD N. 091254 Batu Onom can be said to be effective.